Medium-term economic strategy paper 1996-1999 (Govt. of St.Vincent and the Grenadines KingstownVC, 1996)
Sets out the programme of policies and policy implementation arrangements which, based on the latest information and advice currently available to it, the Government of St. Vincent and the Grenadines has determined would be conducive to sustainable economic growth and development over the medium and long term.
DC